Asian American faculty's racialised experiences in Christian higher education. Issue 2 (7th February 2022) - Hyun, Jung H.; Kim, Paul Youngbin; Cheon, Hee-Sun; Leong, David
ABSTRACT: Given the lack of studies on the racialised experience of Asian American faculty in Christian higher education, the current study investigated Asian American Christian faculty's experiences of stereotypes and discrimination and their responses to those experiences. Using the Consensual Qualitative Research method, we analysed nine interviews with Asian American Christian faculty. Major themes that emerged were the experience of stereotypes and discrimination at the interpersonal level, perpetuation of stereotypes and discriminatory practices at the institutional or systemic level, responses to stereotypes and discrimination, coping with stereotypes and discrimination, and the impact of Asian identity, stereotypes, and discrimination. Implications for future research and Christian higher education institutions are discussed.